Educação financeira: uma necessidade curricular no ensino da matemática básica - NASCIMENTO, Jéssica Cordovil do (2022)
This research aimed to reflect and generate curricular subsidies on Financial Education for the 6th year of Elementary School, especially during the pandemic period. A methodological study was carried out through a quantitative and bibliographical research, on the PCN's and the BNCC. To obtain data, government websites were used, which dealt with financial education in elementary school, especially in the sixth grade. Through detailing, it demonstrated the need to develop in the student the ability to manage their future income, through the personal and family budget, for the responsibility of living in a consumer society and also making the student realize the consequences of a family budget poorly managed. A notebook of proposed exercises was prepared, which aim to teach the student's first steps to the conscious use of money and also ways to make him realize the importance of a calm financial life. The research concludes that although the pandemic period has affected the teaching of mathematics in relation to financial education, it is possible to readjust exercises that can be performed synchronously or even, through exercise books provided by the school, to students who do not have technological means monitoring of online classes.